Chemotype of Flores Indonesia’s Ocimum santum and Cimpogon nardus L - Lerrick, Reinner I.; Pake, Karolina I. (Universitas Nusa Cendana, 2020)
A study of the essential oil content in basil (Ocimum sanctum) and red lemongrass (Cymbopogon nardus L. Rendle) originally grown in Flores island has been conducted. The purpose of this study was to identify the chemotype of the essential oils obtained over stahl distillation using GC-MS. The Ocimum mainly consisted of 55% eugenol following by minor trans-alfa-bergometena, patchulana, and linalool. Meanwhile, the chemotype of the red lemongrass (Cymbopogon nardus L. rendle) were citronellol (22%), citronella, cyclohexamethanol, and viridiflorol.